Study protocol: ASCRIBED: the impact of Acute SystematiC inflammation upon cerebRospinal fluId and blood BiomarkErs of brain inflammation and injury in dementia: a study in acute hip fracture patients - Leavey, Nick (BMC Neurol, 2019)
BACKGROUND: Hip fracture represents a substantial acute inflammatory trauma, which may constitute a significant insult to the degenerating brain. Research suggests that an injury of this kind can affect memory and thinking in the future but it is unclear whether, and how, inflammatory trauma injures the brain. The impact of Acute SystematiC inflammation upon cerebRospinal fluId and blood BiomarkErs of brain inflammation and injury in Dementia: a study in acute hip fracture patients (ASCRIBED) explores this relationship, to understand the effect of inflammation on the progression of dementia. METHODS: This protocol describes a multi-centre sample collection observational study. The study utilises the unique opportunity provided by hip fracture operations undertaken via spinal anaesthesia to collect cerebrospinal fluid (CSF) and blood, to investigate the impact of acute brain inflammation caused by hip fracture on the exacerbation of dementia. We will recruit 200 hip fracture patients with a diagnosis or evidence of dementia; and 200 hip fracture patients without dementia. We will also recruit ‘Suitable informants’, individuals in regular contact with the patient, to provide further proxy evidence of a patient’s potential cognitive decline. We will compare these 400 samples with existing CSF and blood samples from a cohort of dementia patients who had not experienced a systemic inflammatory response due to injury. This will provide a comparison between patients with and without dementia who are suffering a systemic inflammatory response; with stable patients living with dementia. DISCUSSION: We will test the hypothesis that hip fracture patients living with dementia show elevated markers of brain inflammation, as well as neuronal injury and Alzheimer-related plaque pathology, in comparison to (1) stable patients living with dementia and (2) hip fracture patients without dementia, as measured by biomarkers in CSF and blood. The findings will address the hypothesis that systemic inflammatory events can exacerbate underlying dementia and inform the search for new treatments targeting inflammation in dementia. TRIAL REGISTRATION: ISRCTN43803769. Registered 11 May 2017.